Social networks in educational process: analysis of the experience of application, trends and prospects of development. (Journal of Educational Sciences, 2016)
The research objective is the revelation and analysis of the Internet social networks educational potential. For achieving the research objective the following methods of research were used: cognitive generalizing ones, diagnostic ones, the qualitative and quantitative analysis, and the comparison of the obtained data. This paper presents the theoretical aspects of the organization of educational activity in the social networks of the Internet. The article highlights the basic principles and key characteristics of communication in social networks, educational opportunities of social networks, a model of distance and interactive learning on the basis the use of social networks as a pedagogical tool.Also, in this article, the authors provide research and analysis of foreign and Kazakh experience in the application of social networks in the educational process. Based on this analysis the paper contains some positive aspects of social networks applications in the educational space.In order to use educational opportunities for social networks, the authors also consider the prospects of the development of e-learning in the context of the positive aspects of theirusage.
Keywords: internet; social networks; educational process; learning activity